Determinants of non-performing loans of commercial bank in Malaysia / Nur Asyiqin Haziqah Mat Kamal - Mat Kamal, Nur Asyiqin Haziqah (Faculty of Business and Management, 2019)
The purpose of the paper is to study the macroeconomics factors that affect the nonperforming loans (NPLs) of the commercial bank in Malaysia. The data collected from time series data by using quarterly basis from year 2007 until 2010. The multiple linear regressions model is used to discover the significant relationship between the variables and the NPLs. The study concludes that the level of NPLs of Malaysia is affected by macroeconomic variables namely Gross Domestic Product (GDP), Gross National Income (GNI), Inflation Rate (IFR), and Interest Rate (ITR). The result implies that all the variables are significant and negatively related to NPLs except that interest rate is significant and positively related to NPLs. The result of this research is useful to assist financial institutions and the regulators such as Central Bank of Malaysia in order to minimize the negative effects of NPLs to the commercial bank.